ANALYSIS OF INFLUENCE OF ACTIVATOR CONCENTRATION ON CHARACTERISTICS OF ACTIVATED CARBON FROM KETAPANG SHELL (Terminalia Catappa) BASED ON IMAGE PROCESSING METHOD - Herman Aldila; Megiyo Megiyo; Fitri Afriani; Yuant Tiandho (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2018)
Activated carbon from ketapang shell (Terminalia Catappa) has been successfully synthesized using dehydration-carbonization method. Activated carbon was conducted by immersing with sulphuric acid and followed by carbonization at 600oC for 2 hours. Pore characteristics were determined using imageprocessing methods of activated carbon micrographs based on parameters of area and caliper length. From the area approximation method obtained that the maximum pore size estimate was 5,69 μm at activator concentration 3% while the minimum was 4,88 μm at activator concentration 11% activator concentration respectively. At the other hands, caliper length approximation method obtained estimation of maximum pore size that was equal to 9,09 μm at activator concentration 3% and its minimum that was equal to 7,35 μm at activator concentration 7%. The porosity of the activated carbon from ketapang shell increased with the increase of sulfuric acid concentration and the highest value reached 24.96%.